2001
DOI: 10.1126/science.1064150
|View full text |Cite
|
Sign up to set email alerts
|

Transitions in Distinct Histone H3 Methylation Patterns at the Heterochromatin Domain Boundaries

Abstract: Eukaryotic genomes are organized into discrete structural and functional chromatin domains. Here, we show that distinct site-specific histone H3 methylation patterns define euchromatic and heterochromatic chromosomal domains within a 47-kilobase region of the mating-type locus in fission yeast. H3 methylated at lysine 9 (H3 Lys9), and its interacting Swi6 protein, are strictly localized to a 20-kilobase silent heterochromatic interval. In contrast, H3 methylated at lysine 4 (H3 Lys4) is specific to the surroun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
550
4
7

Year Published

2003
2003
2008
2008

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 684 publications
(589 citation statements)
references
References 25 publications
28
550
4
7
Order By: Relevance
“…This finding was somewhat unexpected but consistent with the study by Shnyreva et al (12). Furthermore, in many other recent studies that identified active histone modifications, for example, in the cluster of the globin genes (41), the mating type locus in yeast (42), the Hoxd4 locus (43), active histone modifications do not always correlate with gene expression. Therefore, we believe that for the IFN-␥ gene, the lack of H3K4me2 modification is not an essential condition for silencing its expression in the day 5 Th2 cells.…”
Section: Discussionsupporting
confidence: 86%
“…This finding was somewhat unexpected but consistent with the study by Shnyreva et al (12). Furthermore, in many other recent studies that identified active histone modifications, for example, in the cluster of the globin genes (41), the mating type locus in yeast (42), the Hoxd4 locus (43), active histone modifications do not always correlate with gene expression. Therefore, we believe that for the IFN-␥ gene, the lack of H3K4me2 modification is not an essential condition for silencing its expression in the day 5 Th2 cells.…”
Section: Discussionsupporting
confidence: 86%
“…Hyperacetylation of histone H3 and H4 lysine residues is generally associated with active chromatin, whereas deacetylation has been correlated with inactive genes (35). Another histone modification that has been associated with transcriptionally active chromatin is methylation at Lys 4 of histone H3 (36,37). In cancer cells, histone modifications work in concert with DNA methylation to silence tumor suppressor genes (13,28,38).…”
Section: Discussionmentioning
confidence: 99%
“…Histone methylation could either be associated with actively transcribing RNA polymerase II (Pol II) or could be involved in setting the stage for transcriptional repression within heterochromatin, and sometimes could be both [6,9,[11][12][13]. For example, histone H3 lysine 9 methylation (H3K9), which is implemented by the SUV39 family of enzymes, is mostly associated with the silent regions within both euchromatin and heterochromatin [14][15][16][17][18]. The SUV39 family of HMTs contains a cysteine rich pre-SET domain, which is required for specificity towards H3K9 [18].…”
Section: Nih Public Accessmentioning
confidence: 99%